Penatalaksanaan perdarahan saluran cerna bagian atas dengan nutrisi enteral dini terhadap kadar albumin - Virgianti Nur Faridah; Farida Farida (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2017)
Background: Patients with upper gastrointestinal bleeding generally were decreased nutritional status that hypoalbuminemia because of increased albumin excretion from hemorrhage and patients fasted indefinitely until the bleeding stops. Enteral nutrition in patients with bleeding should be given to prevent malnutrition and reduce mortality.Objective: To identify the differences in levels of albumin serum in the early enteral nutrition without waiting for the results of gastric lavage is clear (without fasting) and after 2-3 times the clear gastric lavage (fasted).Method: The study used pre-experimental research design by static group comparison design. The study was conducted in RS Aisyiyah Bojonegoro in March to June 2015. The sample was 30 patients divided into 2 groups by Random Allocation, there was the treatment group I that fasted (15 patients), and treatment group II without fasted (15 patients). Analysis of data using Wilcoxon test Signed Ranks Test.Results: The research found that there were differences in the provision of early enteral nutrition to albumin. Results showed that albumin level in patients who fasted lower than that without fasted. Results Statistics by Wilcoxon Signed Rank test with a 0.05 significance level values obtained 0,046, its means that H1 was accepted.Conclusion: Patients with upper gastrointestinal bleeding can be given early enteral nutrition without waiting for the results gastric lavage clear rinse.